Efficacy of silver nanoparticles from Jatropha curcas leaf extracts against pyrethroid-resistant Anopheles gambiae - Basosila, Narcisse Bolamba; Mukomena, Eric; Mbembo-Wa-Mbembo, Blaise; Masengo, Colette Ashande; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Orapuh Journal, 2024)
Introduction The increasing resistance of Anopheles gambiae to conventional insecticides poses a significant challenge to malaria control efforts. This study investigates the synthesis of silver nanoparticles (NPAgs) from Jatropha curcas leaf extracts and their potential larvicidal effects on wild Anopheles gambiae larvae, offering a novel approach to vector management. Purpose The purpose of this study was to synthesize NPAgs from J. curcas and assess their larvicidal efficacy against Anopheles gambiae larvae. This research aims to contribute to the development of alternative strategies for mosquito control, addressing the growing issue of insecticide resistance. Methods Silver nanoparticles were synthesized using leaf extracts from J. curcas and characterized by UV-Vis spectroscopy, X-ray diffraction, and X-ray fluorescence spectrometry. Phytochemical screening identified secondary metabolites present in the extracts. The larvicidal effects of NPAgs were evaluated through larvicidal bioassays, and their hemolytic potential was assessed on erythrocyte membranes. Insecticide susceptibility testing was performed using the WHO tube sensitivity test to measure resistance levels. Results Phytochemical analysis indicated the presence of various secondary metabolites, including polyphenols, flavonoids, tannins, alkaloids, quinones, and steroids. Thin-layer chromatography confirmed the presence of flavonoids, terpenoids, alkaloids, and iridoids. UV-Vis spectroscopy revealed an absorbance peak at 500 nm, confirming NPAg synthesis. The characteristic diffractograms showed five peaks corresponding to distinct crystal planes. The hemolysis rate of NPAgs (1 mg/mL) was less than 50%, indicating low cytotoxicity. Larvicidal activity was significant, with 100% mortality observed at a concentration of 1 mg/mL after 24 hours. Resistance testing revealed confirmed resistance at both study sites, with Maluku showing higher resistance than Mbudi. Pre-exposure to 4% PBO increased mortality compared to permethrin alone. Molecular analysis of An. gambiae revealed a composition of 80% An. gambiae, 5% An. coluzzii, and 15% non-amplified samples. Genotypic analysis indicated that 75% of the mosquitoes were homozygous for Vgsc-L1014F, with the remainder showing varying resistance profiles. Conclusion The findings highlight the potential of NPAgs synthesized from J. curcas as effective larvicides against An. gambiae, with implications for future mosquito control strategies. The low cytotoxicity of NPAgs and their efficacy against resistant mosquito populations suggest they could serve as a promising alternative in integrated pest management approaches for malaria vector control.